Wealth inequality and economic mobility in the post-revolutionary Pennsylvania backcountry. Issue 4 (1st October 2020) - Latzko, David A.
Abstract: Township tax lists for 1783 and 1793 are used to examine the distribution of wealth and economic mobility in York County, Pennsylvania following the Revolutionary War. Measures of inequality are inconclusive, but the typical York County household was worse off in 1793 than in 1783: median wealth fell 5 percent. The poorest households recorded an increase in assessed wealth. Over 40 percent of households disappeared from the tax lists, with the least wealthy being the most likely to leave. Households that remained in the county were far more likely to see an improvement in their relative status than a decline.